Evaluating The Role Of Entrepreneurship In Nigeria’s Transition Pathway - A Sustainable Practices Adoption Perspective - Ogochukwu, Emeka (2024)
This study seeks to explore the relationship between entrepreneurs and sustainability transition by looking at the adoption of sustainability practices by entrepreneurs in Nigeria. The study uses interviews to gather qualitative data in order to get a firsthand understanding of the current barriers and drivers that moderate entrepreneurs' willingness and ability to adopt sustainability practices. The data is analyzed using the framework of Three Mechanisms of Institutional Isomorphic Change presented by DiMaggio & Powell (1983) in their paper titled Institutional Isomorphism and Collective Rationality in Organizational Fields. The emergent factors that influence entrepreneurs to adopt more sustainable practices are put into three categories namely coercive, mimetic and normative. Each of these categories offers deeper insights into how the study participants manage sustainability practices currently, and the opportunities for growing the adoption of these practices across entrepreneurs in Nigeria. The research question is: What factors (drivers and barriers) moderate the adoption of sustainability practices among entrepreneurs in Nigeria?